2019
DOI: 10.1039/c8ta10857a
|View full text |Cite
|
Sign up to set email alerts
|

A graphene/ZnO electron transfer layer together with perovskite passivation enables highly efficient and stable perovskite solar cells

Abstract: Interface engineering in organometal halide perovskite solar cells (PSCs) has been an efficient tool to boost the performance and stability of photovoltaic (PV) devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 40 publications
1
111
0
Order By: Relevance
“…These results indicate that the optimum thickness of PDTIDTBT:PC 60 BM is almost 100 nm. Due to high transmittance of the PDTIDTBT, we demonstrate the application of the PDTIDTBT:PC 60 BM blend for the semitransparent OPV by applying CVD graphene on top of the device (31).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the optimum thickness of PDTIDTBT:PC 60 BM is almost 100 nm. Due to high transmittance of the PDTIDTBT, we demonstrate the application of the PDTIDTBT:PC 60 BM blend for the semitransparent OPV by applying CVD graphene on top of the device (31).…”
Section: Resultsmentioning
confidence: 99%
“…This is because of its lower conduction bandgap when compared with conventional electron-transporting materials such as TiO 2 (Figure 3), while graphene acts as an isolation layer that prevents the reaction between ZnO and perovskite triggered by light. 81,83,96…”
Section: Stability Improvement In Different Layers Of Carbon-based mentioning
confidence: 99%
“…[1][2][3][4][5][6] Due to the presence of organic compounds such as methylammonium (MA) in the perovskites, these materials have stability issue, especially in a humid environment, hindering their practical applications. [7][8][9][10][11] Fabrication of all inorganic perovskite films such as cesium lead triiodide (CsPbI 3 ) is an effective way to address this issue. Interestingly, it was found that CsPbI 3 perovskite with a black cubic phase has a bandgap of 1.72 eV, which is suitable for optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%